한의분야 장애인 건강주치의 시범사업에 대한 장애인들의 인식: 심층 인터뷰를 중심으로 - 조재경; 정혜인; 김경한; Jae Kyung Jo; Hye In Jeong; Kyeong Han Kim (동의생리병리학회지, 2024)
This study aimed to investigate the perception on the primary care for people with disabilities by Korean medicine doctors. This study was conducted to analyze the opinions of disabled people about the Korean medicine doctor for the primary care for disabled people by conducting interviews. In-depth interviews were conducted with three disabled people who were able to express their opinions, and each interview lasted approximately 60 minutes, on Mar 2024. All three physically disabled people who participated in the study were eligible for medical benefits and frequently used hospitals and clinics for health care, including rehabilitation treatment. They did not know much about the primary care for the disabled, but after explaining the system, they consented that Korean medicine doctors should be included in the system. Those with severe disabilities who had difficulty moving around on their own preferred home visit treatment, and those with mild disabilities preferred to receive treatment more often instead of visiting the hospital. This study is significant in that it allows us to understand what the disabled people, who are actual consumers, think about Korean medicine doctors' participation in the primary care for the disabled.